Empat Perspektif Citra dan Harapan terhadap Kawasan Kesawan Kota Medan: Konservasi, Pariwisata, Revitalisasi, dan Pengembangan - Tampubolon, Meta Vaniessa; Kusuma, Hanson E. (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2020)
Characteristics and history contained in buildings and environments in the city will create an image of the area which was then called as historic area. Kesawan area in Medan City is one of the historical areas and the identity of the city. The current problems are economic interests, modernization, uneven urban development, and improperly enforced laws that threaten the existence of historic areas and buildings. This study aims to reveal the image and expectations of the Kesawan Area from the viewpoint of the people of Medan City, which can be used as a foothold in formulating policies in maintaining its preservation as a historic area. The methods used in this study are mixed methods, namely qualitative and quantitative. The data collection method is done using an online questionnaire with a non-random sample - snowball sampling. Qualitative data analyzed contents. Quantitative data were analyzed by factor analysis and multivariate correlation analysis. From the analysis of images and expectations revealed four perspectives on the Kesawan Area. First, a conservation perspective that hopes that Chinatown's identity in the Kesawan Area is maintained. The two tourism perspectives that have a dominant image of the Kesawan Area tourist attraction and the Kesawan Area hope remain the Medan City icon. The three revitalization perspectives that have the image of the Kesawan Area are difficult to park, crowded during the day, but have a visual appeal, and hope that the Kesawan Region becomes a living area. The four development perspectives expect infrastructure improvements in the Kesawan area.